Legal Protection Model for Victims of Sexual Violence at Universities Case Study: UIN North Sumatra - Farhan Fathur Rahman; Himmatul Khoiriyah (Program Pascasarjana UIN Sumatera Utara Medan, 2019)
In Indonesia, sexual violence is nothing new. It occurs not only in the workplace, family, and community. Sexual violence also occurs in universities. This is the reason for the issuance of Regulation of the Minister of Education, Culture, Research, and Technology Number 30 of 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education, which requires every university to develop policies regarding the protection of victims of sexual violence in universities. Therefore, the purpose of this study, by examining this incident, is to clarify the Legal Protection Model for Victims of Sexual Violence at the State Islamic University of North Sumatra. The research method used in this study is the Empirical Juridical method with the Statue Approximation approach. After conducting the study, it was discovered that the protection received by victims of sexual violence at the State Islamic University of North Sumatra is in the form of assistance and guarantees of identity confidentiality. Victims of sexual violence also receive legal certainty from the perpetrator and also receive physical and psychological recovery as a result of the sexual violence they experienced.